2020
DOI: 10.3389/fendo.2020.606560
|View full text |Cite
|
Sign up to set email alerts
|

Mini-Review: The Contribution of Adipokines to Joint Inflammation in Inflammatory Rheumatic Diseases

Abstract: Inflammatory rheumatic diseases (IRD) are complex disorders characterized by chronic inflammation of the joints and related skeletal structures. The most common forms of IRD are rheumatoid arthritis (RA) and spondyloarthritis (SpA), including axial SpA (axSpA) and psoriatic arthritis (PsA). Obesity is a frequent comorbidity in RA and PsA, and to a lesser extend in axial SpA. The association between obesity and IRD may be explained by the release from fat tissue of several bioactive proteins, namely adipokines.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 86 publications
0
23
0
Order By: Relevance
“…For instance, tumor necrosis factor (TNF)-a, interleukin (IL)-6, and IL-1b play major roles in joint inflammation, and biological agents against these molecules have been developed in the field of RA therapy [1]. Adipokines are multifunctional signal transduction molecules, and their relationship with osteoimmunology has attracted attention in recent years [2][3][4][5][6][7][8][9][10][11]. In this review, we discuss the role and contribution of leptin, one of the best-characterized adipokines, in the pathogenesis of RA.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, tumor necrosis factor (TNF)-a, interleukin (IL)-6, and IL-1b play major roles in joint inflammation, and biological agents against these molecules have been developed in the field of RA therapy [1]. Adipokines are multifunctional signal transduction molecules, and their relationship with osteoimmunology has attracted attention in recent years [2][3][4][5][6][7][8][9][10][11]. In this review, we discuss the role and contribution of leptin, one of the best-characterized adipokines, in the pathogenesis of RA.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, compared with HCs or patients with osteoarthritis, serum resistin levels were increased in patients with RA and positively correlated with inflammatory markers such as ESR, CRP, and disease activity, which determined by measuring disease activity score 28 values. These studies indicated that resistin play a role in the regulation of inflammatory processes in RA ( 10 , 24 ). Baker et al revealed that serum resistin levels were increased in patients with SLE than in control subjects, and higher resistin levels were positively correlated with renal insufficiency, inflammatory markers, and disease damage ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that resistin levels were elevated in the synovial fluid of patients with RA and were positively associated with RA disease activity and joint damage ( 10 ). Similarly, compared with HCs or patients with osteoarthritis, serum resistin levels were increased in patients with RA and positively correlated with inflammatory markers such as ESR, CRP, and disease activity, which determined by measuring disease activity score 28 values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adipose tissue may be considered an organ [ 30 ] owing to its ability in secreting cytokines, interleukins, growth factors and adipokines. Such growth factors are present in synovial fluid [ 31 ] and can determine the metabolism of cartilage and synovium [ 32 ]. In particular, leptin and adiponectin are adipokines secreted in large quantities only by adipose tissue, but found also in the synovial fluid.…”
Section: Pathogenesis and Histology Of Osteoarthritis Diseasementioning
confidence: 99%